Influence of the haloaryl moiety over the molecular packing in N-phenacylbenzimidazoles crystallizing in the same space group (2021)
In this study, a family of N -phenacylbenzimidazoles 1–3 synthesized in high yields (90–93%) by the N - phenacylation reaction of NH -benzimidazole ( 4 ) under ultrasonic conditions was recrystallized from the mixture EtOH:AcOEt (1:1 V/V). These compounds crystallize in the same Monoclinic P 2 1 / c space group, though the molecular packing is affected by the haloaryl group varying the final crystal structure. The para substitution of the halogen atom in the aryl ring influences a more pronounced electronic defi- ciency over the methylene bridge allowing the formation of intermolecular C–H ···O hydrogen bonds in compounds 1 and 3 . Additionally, in compound 2 , the ortho substitution of an F atom, not only affects the electron density but also blocks this CH 2 group with an intramolecular C–H ···O hydrogen bond. Re- markably after the crystallization process, compound 3 crystallizes as a cocrystal with a 4-fluorobenzoic acid molecule obtained by hydrolysis of 3 . This co-crystallization affects dramatically the total packing energies from values of -138.7/-135.2 kJ/mol for 1 and 2 , respectively, to -229.7 kJ/mol for compound 3 .